A Novel Approach for Optimal Multimedia Data Distribution in Mobile Cloud Computing. (23rd October 2014) - Phuoc Hung, Pham; Aazam, Mohammad; Nguyen, Tien-Dung; Huh, Eui-Nam
Abstract : With the integration of mobile computing and cloud computing, more diverse services can be provided to the users, supporting the mobility feature of mobile computing along with the power of cloud computing. This new paradigm still faces challenges, especially in terms of performance. When it comes to multimedia data communication, thin clients (such as smart phones and tablets) suffer because of performance and power constraints. Previously done studies have trivially addressed this problem. Therefore, in our paper, we present a framework in which thick clients (laptop or desktop computers) are incorporated into mobile cloud paradigm with attention paid to user mobility. Its objective is to optimize the distribution of multimedia content between the cloud and the thin clients. Our work comes up with both numerical analysis and simulation to justify the validity and the effectiveness of the proposal approach.